The Credit Risk Transfer Market and Stability Implications for U.K. Financial Institutions - Ong, Li (IMF Working Papers; Working Paper ;, 2006)
The increasing ability to trade credit risk in financial markets has facilitated its dispersion across the financial and other sectors. However, specific risks attached to credit risk transfer (CRT) instruments in a market with still-limited liquidity means that its rapid expansion may actually pose problems for financial sector stability in the event of a major negative shock to credit markets. This paper attempts to quantify the exposure of major U.K. financial groups to credit derivatives, by applying a vector autoregression (VAR) model to publicly available market prices. Our results indicate that use of credit derivatives does not pose a substantial threat to financial sector stability in the United Kingdom. Exposures across major financial institutions appear sufficiently diversified to limit the impact of any shock to the market, while major insurance companies are largely exposed to the "safer" senior tranches.